The rural and agricultural value of groundwater as an economic resource in the Limpopo region - Mahumani, Brian Kudzai (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Agricultural Economics)--University of Stellenbosch, 2009.